Improvement of wood decay resistance by salicylic acid / silica microcapsule: Effects on the salicylic leaching, microscopic structure and decay resistance. (January 2021) - Yan, Li; Zeng, Feiyang; Chen, Zhangjing; Chen, Shuang; Lei, Yafang
Abstract: Wood is an environmentally friendly product, but some of woods can be easily biodegraded. Salicylic acid/silica microcapsules (SSM) represents a kind of wood preservative prepared with the anti-fungal salicylic acid as a core substance and the silica as wall material using sol-gel technology. SSMs were synthesized and then impregnated into poplar wood using vacuum-pressure treatment. Leaching tests were carried out in distilled water for up to 318 h. Decay resistance of SSM treated poplar against white-rot fungi ( Trametes versicolor ) and brown rot fungi ( Gloeophyllum trabeum ) was determined. Leaching tests showed that SSM retention was good and leaching resistance of salicylic acid in SSM treated wood were improved. SEM (scanning electron microscope), FTIR (Fourier-transform infrared spectroscopy), EDX (Energy Dispersive X-Ray Spectroscopy) and XPS (X-ray photoelectron spectroscopy) analysis showed that the SSMs were between 0.06 and 0.16 μm, and most were distributed in the vessel cavity with hydrogen bonding to cell wall surfaces, some SSMs were found in the cell wall. The decay resistance of SSM treated poplar was greatly improved compared to untreated poplar. Graphical abstract: Image 1 Highlights: The anti-leaching of plant-extracted wood protectors was increased by microcapsule. SSM can be potentially applied as an environment-friendly wood preservative. Basis for utilization of microcapsule on organic wood protectors was provided. SSM treatment might improve the durability of perishable wood.